2019
DOI: 10.1016/j.tibs.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Universal Nature of Collapsibility in the Context of Protein Folding and Evolution

Abstract: Theory and simulations predicted sometime ago that the sizes of unfolded states of globular proteins should decrease continuously as the denaturant concentration is shifted from a high to a low value. However, small angle X-ray scattering (SAXS) data were used to assert the opposite, while interpretation of single molecule Forster resonance energy transfer experiments (FRET) supported the theoretical predictions. The disagreement between the two experiments is the SAXS-FRET controversy. By harnessing recent ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 86 publications
4
40
0
Order By: Relevance
“…At L = 316, the nascent chain has properties of an intrinsically disordered protein, whereas the addition of just 12 amino acids to L = 328 results in the formation of collapsed or partially structured states and subsequent folding to the native structure. Theoretical studies concluded that the formation of compact states is an evolved property of natural proteins 47 . The G-domain may be an attractive model to investigate how this property is related to protein sequence and structure.…”
Section: Discussionmentioning
confidence: 99%
“…At L = 316, the nascent chain has properties of an intrinsically disordered protein, whereas the addition of just 12 amino acids to L = 328 results in the formation of collapsed or partially structured states and subsequent folding to the native structure. Theoretical studies concluded that the formation of compact states is an evolved property of natural proteins 47 . The G-domain may be an attractive model to investigate how this property is related to protein sequence and structure.…”
Section: Discussionmentioning
confidence: 99%
“…The value of ν suggests that Aβ monomers behave as polymers in a good solvent. However, we should note that ν estimates from either simulations or experiments suffer from finite-size effects (56).…”
Section: Few Metastable States Cannot Represent the Aβ Ensemblesmentioning
confidence: 99%
“…(ii) It should be noted that the change in the mean value of R g , with respect to the unfolded states is less than about 20%, which is a common observation in a number of proteins. 60 Our results show that it is difficult to unambiguously assess barriers to collapse in folding. In light of extensive theoretical studies, summarized elsewhere, 60 we surmise that the barrier to collapse in Cyt c should exist 56 but multiple probes might be needed to estimate the magnitude.…”
Section: Resultsmentioning
confidence: 84%